Philippine real estate investment factbook & directory 1995-1996. (Chamber of Real Estate & Builders' Associations, 1995)
Created by the Chamber of Real Estate Builders' Associations, Inc.(CREBA), this book is divided into two parts: the fact book and the directory. These provide useful information on the real estate scene, as well as alphabetical listings of CREBA members and other organizations. The other sections of the book are separated by paper tabs for easy navigation.